2000
DOI: 10.1023/a:1010930819854
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The epithelial cells of the choroid plexus are a continuation of the ventricular ependymal cells and are regarded as modified ependymal cells. The present study was carried out to determine the influence of choroid plexus ependymal cells (CPECs) on axonal growth in vitro. Choroid plexuses were dissected from the fourth ventricle of postnatal day-1-10 mice, mechanically dissociated, and plated in fibronectin-coated culture dishes. CPECs had spread into monolayers with few endothelial cells in 3-week cultures. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Immoderate synaptic transmissions in the spinal dorsal horn coupled with aberrant neuronal firing have been hypothesized to contribute to the development of neuropathic pain. , Neurite outgrowth, including neurite extension and neuronal branching, is the structural foundation of neuronal plasticity . Structural neuroplasticity has the noticeable property of being capable of altering the efficiency of synaptic transmissions according to the discharge patterns of neurons receiving nociceptive stimulation. In agreement with the prior report, we employed an anti-β-tubulin III antibody (a microtubule element of the tubulin family), which was present almost exclusively in neurons to identify neurite outgrowth …”
Section: Discussionsupporting
confidence: 58%
“…Immoderate synaptic transmissions in the spinal dorsal horn coupled with aberrant neuronal firing have been hypothesized to contribute to the development of neuropathic pain. , Neurite outgrowth, including neurite extension and neuronal branching, is the structural foundation of neuronal plasticity . Structural neuroplasticity has the noticeable property of being capable of altering the efficiency of synaptic transmissions according to the discharge patterns of neurons receiving nociceptive stimulation. In agreement with the prior report, we employed an anti-β-tubulin III antibody (a microtubule element of the tubulin family), which was present almost exclusively in neurons to identify neurite outgrowth …”
Section: Discussionsupporting
confidence: 58%
“…Choroid plexus epithelial cells (CPECs) are originated from the ventricular ependymal cells and are considered as modified ependymal cells. 43 Ependymal cells include multiciliated cells of the cubic epithelium lining the cavities of the ventricles of the brain and the central canal of the spinal cord of vertebrates. More than half-century ago, it was shown that due to the movement of cilia, ependymocytes create the flow of cerebrospinal fluid inside the lateral ventricles of the brain, 44 then, the protective function of the ependyma was clearly demonstrated as an ability of these cells to regulate the transport of molecules between the cerebrospinal fluid and choroidal capillary.…”
Section: Complexity Of the Neurovascular Unit And Key Brain Tissue Ba...mentioning
confidence: 99%
“…All primary and branching neurites were manually traced on the digital images. The following parameters were measured as previously described (Chakrabortty et al 2000); 1) total neurite length/neuron, 2) total primary neurite length/neuron, 3) mean length of primary neurite/neuron, 4) mean number of primary neurites/neuron, and 5) mean number of branching neurites/neuron. Data are presented as mean ± standard deviation.…”
Section: Measurements Of Neurite Outgrowthmentioning
confidence: 99%